The Identification Of Morphometric Characteristics And Fattenning Of Mud Crabs (Scylla spp.) In Para Island, Tatoareng District, Sangihe Islands Regency, North Sulawesi Province - Aditya Sasamu; Winda M. Mingkid; Revol D. Monijung (Jurnal Ilmiah PLATAX, 2019)
The purpose of this study was to identify the morphometric characters of mangrove crabs Scylla spp. and to grow them on the island of Para Sangihe Islands Regency, North Sulawesi Province. There were 2 types of crabs found during crab’s collection. However, the most abundant one was Scylla serrata while the olivacea is only one tail. The results of this study indicate that mangrove crabs that were kept for 2 weeks feed on trash fish three times a day experience growth. Based on the results of the study, it can be concluded that: the type of crab found on Pulau Para, Tatoareng District, Sangihe Islands Regency, North Sulawesi Province were mostly S. serrata (34 tails) and one tail of S. olivacea. The fattening of mangrove crabs showed results on the body weight and carapace length.Further research on mangrove crabs needs to be done on different aspects such as preferable food and time of the abundancy.Keywords: Crab, Scylla spp., identification, fattening. ABSTRAK       Tujuan dari penelitian ini adalah untuk mengidentifikasi karakter morfometrik kepiting bakau Scylla spp dan cara penggemukannya di Pulau Para Kabupaten Kepulauan Sangihe Provinsi Sulawesi Utara. Dua jenis kepiting bakau ditemukan saat pengumpulan data, namun yang ditemukan paling banyak adalah Scylla serrata, sedangkan S. olivacea hanya 1 ekor saja.Hasil penelitian ini menunjukan bahwa kepiting bakau yang dipelihara selama 2 minggu dengan diberi pakan ikan rucah sebanyak tiga kali sehari mengalami pertumbuhan. Berdasarkan hasil penelitian dapat disimpulkan bahwa: jenis kepiting yang ditemukan di Pulau Para Kecamatan Tatoareng Kabupaten Kepulauan Sangihe Provinsi Sulawesi Utara adalah Scylla serrata (34 ekor) dan S. olivacea (1 ekor). Penggemukan kepiting bakau dengan pakan ikan rucah tiga kali sehari menunjukan adanya pertumbuhan berat badan dan panjang lebar karapas.     Penelitian lanjutan tentang kepiting bakau perlu dilakukan untuk melihat berbagai aspek seperti makanan kesukaan dan waktu kelimpahanya.Kata kunci : Kepiting, Scylla spp, identifikasi, penggemukan.